Valor prognóstico de marcadores de diferenciação neuroendócrina e de células-tronco em pacientes submetidos a prostatectomia radical por câncer de próstata localizado - Hirth, Carlos Gustavo (2016)
This study aimed to evaluate the new immunohistochemical markers related to neuroendocrine differentiation induction and stem cells with prognostic factors and biochemical recurrence in patients submitted to radical prostatectomy. Therefore, patients operated at the Hospital Walter Cantídio, Federal University of Ceará, in the period of 2008-2013, underwent clinical and outpatient follow-up, between the years 2008-2016. Biochemical recurrence was evaluated and was correlated with pathological characteristics and immunohistochemical reactions. Chromogranin (neuroendocrine differentiation), Aurora Kinase A (AURKA), N-MYC, C-MYC and CD44s were performad in paraffined material. From 74 patients underwent surgery was obtained the followup of 69, in a median period of 41 (2-89) months. Neoplastic neuroendocrine differentiation was associated with seminal vesicles infiltration (p = 0.032) and stage (p = 0.030). C-MYC was associated with Gleason score (p = 0.001) and seminal vesicles infiltration (p = 0.014). AURKA was expressed in rare cases. N-MYC protein was negative in all patients. CD44s was associated with lower preoperative PSA levels and lower Gleason scores. Biochemical recurrence was observed in 27.0% of patients. Recurrence was associated with serum preoperative PSA, Gleason score, seminal vesicle invasion and staging at least in one form of analysis. There was no significant association between recurrence and neuroendocrine differentiation, C-MYC and CD44s expression. Therefore, immunohistochemical detection of neuroendocrine differentiation, expression of C-MYC and loss of CD44s were related to more aggressive carcinomas (PSA, Gleason, seminal vesical invasion and/or stage), but no association with biochemical recurrence. Classic prognostic factors were affirmed like biochemical recurrence predictores.